Analysis of the Community Satisfaction Index (CSI) toward Public Services at Bengkulu City Regional Water Utility (PDAM) - Gilang Fajar Utama; Tito Irwanto; Iswidana Utama Putra (Journal of Applied Financial Management, 2026)
Public service delivery represents one of the government's primary functions in fulfilling citizens' basic needs and improving the relationship between the state and society. One essential form of public service is the provision of clean water managed by Regional Water Utilities (PDAM). As a public service provider, the Bengkulu City Regional Water Utility (PDAM Tirta Hidayah) is expected to deliver high-quality, effective, and citizen-oriented services. This study aims to analyze the Community Satisfaction Index (CSI) regarding public services provided by PDAM Tirta Hidayah Bengkulu City. A descriptive quantitative approach was employed in this research. Data were collected through a community satisfaction survey administered to PDAM service users using a questionnaire developed based on the Regulation of the Minister of Administrative and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017 concerning Guidelines for Community Satisfaction Surveys in Public Service Delivery Units. The CSI was measured using nine service elements, namely service requirements, systems, mechanisms and procedures, completion time, costs or tariffs, service product specifications, service provider competence, service provider behavior, complaint handling, and facilities and infrastructure. The results indicate that the overall level of community satisfaction with the services provided by PDAM Tirta Hidayah Bengkulu City falls within the excellent category. Among the nine service elements evaluated, the highest scores were achieved by the elements of systems, mechanisms, and procedures and complaint handling, suggestions, and feedback, with converted index scores of 88.25 and 85.25, respectively. These findings demonstrate the clarity of service processes and the responsiveness of the service provider in addressing public complaints and feedback. Therefore, the quality of public services provided by PDAM Tirta Hidayah Bengkulu City can be considered highly satisfactory from the perspective of service users.